Law in the News as a Prevention of Criminal Acts Related to Uang Panai in the Tradition of Marriage in Indonesia - Subair, Muh.; Idham PA, Naurah Fakhirah; Isnanto, Muh.; Suarsana, I Made; Satyananda, I Made (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
The tradition of Uang panai is the wisdom of the Bugis-Makassar tribe in Indonesia to honor women in the marriage process. Unfortunately, the amount of Uang panai is often the reason for criminal acts, such as fraud and theft, to fulfill the Uang panai. This study explores how audiences' reception of law news related to uang panai is based on Stuart Hall's theory and how it impacts the prevention of crime associated with this tradition. This article is written qualitatively, using a reception analysis of media news. The search for media news data was supported by in-depth interviews with purposively selected informants and complemented by literature studies. This research focuses on the theft of uang panai, which went viral and was widely responded to by the community. The results show three positions of audience acceptance, namely the dominant position that supports consistent law enforcement to create a deterrent effect. The negotiation position also supports law enforcement but offers customary reforms to make it cheaper and encourages people to act more wisely by facilitating uang panai. The existence of a community that promotes the uang panai tradition will reduce the pressure on men who are committed to marriage and be a deterrent to the criminal act of uang panai. The opposition rejects the application of formal law to perpetrators of theft for uang panai and suggests settlement by customary law. The opposition believes that understanding the sacredness of adat will effectively prevent crimes related to uang panai. The impact of legal reporting related to uang panai to avoid criminal acts appears in the form of public awareness of the consequences. Awareness of the consequences is born from the impact of the news that gives a deterrent effect, strengthens traditions, and encourages policy improvements.